A method for preparing a hydrogen fuel cell membrane electrode and a membrane electrode
By pre-coating the graphene film between the proton exchange membrane and the catalytic layer, the problems of proton exchange membrane swelling and catalytic layer cracking during the preparation of the membrane electrode through direct coating method are solved, and the high quality and stable performance of the membrane electrode are achieved.
Patent Information
- Application Number
- CN202310037677.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-01-09
AI Technical Summary
In the prior art, when preparing membrane electrodes by direct coating method, the proton exchange membrane is prone to swell, and the catalytic layer is prone to crack during drying, affecting the performance of the membrane electrode.
A graphene film is pre-coated between the proton exchange membrane and the first catalytic layer. The graphene film acts as the back film of the proton exchange membrane to prevent swelling and maintain the integrity of the catalytic layer during drying.
It effectively prevents the swelling of the proton exchange membrane and cracking of the catalytic layer, improves the quality and power generation performance of the membrane electrode, reduces hydrogen permeability, and improves operating stability and durability.
Smart Images

Figure CN115986140B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen fuel cells, and in particular relates to a method for preparing a hydrogen fuel cell membrane electrode and the membrane electrode. Background Art
[0002] A fuel cell is a device that converts chemical energy into electrical energy. It is a basically pollution-free energy conversion device. The membrane electrode is the core component of the fuel cell. In the membrane electrode, the catalyst / proton exchange membrane assembly (CCM) formed by loading the fuel cell catalyst on both sides of the proton exchange membrane is the actual place where the electrochemical reaction occurs. Its structure directly affects the performance of the membrane electrode.
[0003] At present, the preparation methods of CCM electrodes mainly include spraying, transfer and direct coating. Among them, although the spraying method can produce a catalyst layer with better performance, its problem is that the spraying loss is large and the time is long, which seriously limits its production capacity. The transfer method is to first form the catalyst layer on other base membranes (such as PTFE membranes), and then transfer it from the base membrane to the proton exchange membrane at a certain temperature and pressure to form CCM. Although this method avoids the swelling of the proton exchange membrane caused by direct contact between the solvent and the proton exchange membrane, the transfer process requires a large pressure, which will cause the pore structure of the catalyst layer to be destroyed and affect the performance of CCM. Compared with the first two methods, the direct coating method is to directly apply the catalyst slurry to the proton exchange membrane and then form the catalyst layer after drying. However, there is also a more serious problem in the preparation of CCM by direct coating, that is, when the slurry is applied to the proton exchange membrane, the proton exchange membrane is very easy to absorb the solvent in the slurry and swell, which seriously affects the quality of the membrane electrode. At the same time, the catalyst layer is prone to cracking in the subsequent drying process, which affects the performance of the membrane electrode.
[0004] At present, there are patents that have proposed solutions to this problem. For example, patent CN112259753A uses diammonium butyl as an additive, which is beneficial to the interaction between its nitrogen-containing functional groups and the sulfonic acid groups of the proton exchange membrane, so that the entanglement between the polymer chains of the perfluorosulfonic acid resin increases, avoiding the problem of cracking of the catalyst layer during the drying process. Patent CN113299927A coats the cathode catalyst layer on the first proton exchange membrane in the presence of a backing film to obtain a cathode half CCM, and coats the anode catalyst layer on the second proton exchange membrane to obtain an anode half CCM, then removes the backing film, and combines the cathode half CCM and the anode half CCM together by hot pressing to obtain a CCM.
[0005] However, the above patent CN112259753A requires the addition of a high-boiling-point toxic solvent to prevent the swelling of the proton exchange membrane during direct coating. The boiling point of the added diammonium butyl is around 160°C, and a very high temperature is required when the catalyst layer is dried, which will damage the proton exchange membrane. On the other hand, it is a highly toxic solvent, which poses a great safety risk during use and increases subsequent processing costs. The above patent CN113299927A uses hot pressing to combine the two half CCMs together, which will inevitably destroy the pore structure of the catalyst layer and deteriorate the power generation performance of the membrane electrode. At the same time, the proton exchange membrane may not be tightly combined by hot pressing, which will affect the proton conduction efficiency of the membrane electrode.
[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0007] In order to solve the technical problems in the prior art that swelling is easy to occur during the preparation of membrane electrodes by direct coating method and cracking of the catalyst layer is easy to occur during the drying process, a method for preparing a hydrogen fuel cell membrane electrode and a membrane electrode are provided.
[0008] A first aspect of the present invention provides a method for preparing a hydrogen fuel cell membrane electrode, characterized in that it includes: coating a graphene membrane between a proton exchange membrane and a first catalytic layer, and when coating the second catalytic layer, the graphene membrane is the back membrane of the proton exchange membrane.
[0009] In some embodiments, the second catalytic layer is directly coated on the surface of the proton exchange membrane.
[0010] In some embodiments, a graphene membrane is coated between the second catalytic layer and the proton exchange membrane.
[0011] In some embodiments, the raw materials of the graphene membrane are graphene, Nafion and water, and the solid content of Nafion in the graphene membrane is 20% to 30%.
[0012] In some embodiments, the graphene membrane is obtained by coating a graphene slurry onto the proton exchange membrane and then drying the resulting film, and the mass concentration of graphene in the graphene slurry is 10 mg / ml.
[0013] In some embodiments, the graphene film has a thickness of 2 to 5 μm.
[0014] In some embodiments, raw materials of the first catalytic layer and the second catalytic layer are platinum carbon catalyst, Nafion, water and isopropanol, the mass ratio of the carbon in the Nafion and the platinum carbon is 0.6-0.8, and the mass ratio of the water and isopropanol is 1:1-1:5.
[0015] In some embodiments, in the first catalytic layer and the second catalytic layer;
[0016] And / or, the platinum loading is 0.1-0.3 mg / cm 2 .
[0017] A second aspect of the present invention provides a hydrogen fuel cell membrane electrode, comprising a proton exchange membrane, wherein both sides of the proton exchange membrane are coated with catalyst layers, wherein a graphene membrane is coated between the catalyst layer on at least one side and the proton exchange membrane.
[0018] In some embodiments, the hydrogen fuel cell membrane electrode is prepared by the above-mentioned preparation method.
[0019] In some embodiments, a method for preparing a hydrogen fuel cell membrane electrode mainly comprises the following steps:
[0020] (1) First, graphene slurry and catalyst slurry are prepared, wherein the main components of the graphene slurry are graphene, water and a commercial Nafion solution with a mass fraction of 5%, the mass concentration of graphene is 10 mg / ml, and the solid content of Nafion after drying is 20%-30%. The main components of the catalyst slurry are platinum-carbon catalyst, a commercial Nafion solution with a mass fraction of 5%, water and isopropanol, wherein the mass ratio of carbon in Nafion and platinum-carbon after drying (I / C) is 0.6-0.8, and the mass ratio of water to isopropanol is 1:1-1:5.
[0021] (2) Fix the proton exchange membrane, tear off the protective film on the surface of the proton exchange membrane, retain the back film, apply the graphene slurry on the proton exchange membrane and dry it, and control the thickness of the wet film so that the thickness of the graphene layer after drying is 2 to 5 μm. During the graphene membrane coating and drying process, the proton exchange membrane will not swell and deform due to the tensile resistance of the back film.
[0022] (3) A layer of catalyst slurry is coated on the graphene film obtained in the above step and dried, and the platinum loading of the catalyst layer is controlled to be 0.1-0.3 mg / cm by controlling the thickness of the wet film. 2 The drying conditions are 40-70℃ for 30min. This layer is the first catalytic layer.
[0023] (4) After fixing the proton exchange membrane coated with a graphene layer and a catalyst layer on one side, the backing film is torn off, and the catalyst slurry is coated on the side without the membrane layer and then dried. The preparation process of the catalyst layer is consistent with step (3), and the platinum loading is 0.1-0.3 mg / cm 2 , which is the second catalyst layer. During the coating and drying process of the second catalyst layer, due to the anti-stretching effect of the graphene membrane, the proton exchange membrane will not swell significantly, and a catalyst layer with a smooth surface can be obtained.
[0024] Compared with the prior art, the technical effects achieved by the present invention are as follows:
[0025] (1) The present invention pre-coats a graphene anti-stretching layer between the proton exchange membrane and the first catalyst layer, and does not require the addition of additional additives or other additional operations to the catalyst slurry. When the catalyst slurry on the other side is coated with the backing film removed, the proton exchange membrane is substantially free of swelling, and a membrane electrode with good quality can be produced.
[0026] (2) After the catalyst slurry is pre-coated with a graphene tensile-resistant layer, the catalyst slurry can be directly applied to both sides of the same proton exchange membrane without the need for additional hot pressing operations, thereby effectively avoiding the destruction of the pore structure of the catalyst layer and causing the membrane electrode power generation performance to deteriorate.
[0027] (3) The present invention pre-coats a graphene layer between the proton exchange membrane and the first catalyst layer, which can effectively reduce the permeation of hydrogen from the anode to the cathode and improve the operating stability and durability of the membrane electrode.
[0028] (4) Using graphene as the anti-stretching layer can not only prevent the second catalyst from cracking during the coating and drying process, but also make the membrane electrode easier to operate in subsequent packaging and stack assembly due to its high strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the membrane electrode preparation process in Example 1 of the present invention;
[0030] Figure 2 This is a photo of the second catalyst layer coating and drying process when preparing the membrane electrode in Example 1;
[0031] Figure 3 It is a schematic diagram of the membrane electrode preparation process in Comparative Example 1 of the present invention;
[0032] Figure 4 This is a surface photograph of the second catalytic layer coating and drying process when preparing the membrane electrode in Comparative Example 1 of the present invention;
[0033] Figure 5 This is a comparison chart of the power generation performance of the membrane electrode prepared in Example 1 and Comparative Example 1 of the present invention;
[0034] Description of reference numerals:
[0035] 101 - proton exchange membrane; 102 - back membrane; 2 - graphene tensile strength layer; 301 - first catalytic layer; 302 - second catalytic layer. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is described below by specific embodiments in conjunction with the accompanying drawings. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and is not intended to limit the order of arrangement of each method or to define the scope of implementation of the present invention. Changes or adjustments in their relative relationships can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.
[0037] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0038] Example 1: A method for preparing a battery membrane electrode
[0039] Preparation of graphene slurry: Weigh 0.1 g of graphene, add 9.4 g of water and 0.5 g of 5% commercial Nafion solution, respectively, and disperse evenly by ultrasonication for later use;
[0040] Preparation of catalyst slurry: Weigh 0.2 g of 40% platinum carbon, add 0.26 g of water, 1.3 g of isopropanol, and 1.92 g of 5% commercial Nafion solution respectively, and disperse evenly by ultrasonication for later use.
[0041] like Figure 1 As shown, after the proton exchange membrane is fixed, the surface protective film is torn off (the back film on the other side is retained), the prepared graphene slurry is applied to the proton exchange membrane and dried, and the thickness of the graphene layer after drying is controlled to be 2 μm by adjusting the wet film thickness. After the solvent in the graphene layer is fully volatilized, the prepared catalyst slurry is applied to the graphene layer and dried at 70°C for 30 minutes to obtain the first catalytic layer, and the platinum loading of the catalytic layer is controlled to be 0.1 mg / cm 2 The proton exchange membrane with the graphene layer and the first catalyst layer on one side was removed and fixed after the backing film was removed. The side without the membrane layer was facing upward and coated with the catalyst slurry. The second catalyst layer was obtained by drying at 70°C for 30 min. The platinum loading of the catalyst layer was controlled to be 0.3 mg / cm 2 .
[0042] Figure 2 This is a photograph of the second catalytic layer coating and drying process when preparing the membrane electrode in Example 1. It can be seen from the figure that without the protection of the back membrane, the proton exchange membrane has no obvious deformation and the prepared membrane electrode is of good quality.
[0043] Example 2: A method for preparing a battery membrane electrode
[0044] The difference between this embodiment and embodiment 1 is that the thickness of the wet film is adjusted so that the thickness of the graphene layer after drying is 5 μm.
[0045] Example 3: A method for preparing a battery membrane electrode
[0046] The difference between this embodiment and embodiment 1 is that the mass of water added to the graphene slurry is 9 g, and the mass of Nafion with a mass fraction of 5% is 0.85 g.
[0047] Example 4: A method for preparing a battery membrane electrode
[0048] The difference between this embodiment and embodiment 1 is that the mass fraction of Nafion added to the catalyst slurry is 1.48 g with a mass fraction of 5%.
[0049] Example 5: A method for preparing a battery membrane electrode
[0050] The difference between this embodiment and embodiment 1 is that the amount of catalyst slurry water and isopropanol added is both 0.8 g.
[0051] Example 6: A method for preparing a battery membrane electrode
[0052] The difference between this embodiment and embodiment 1 is that the platinum loading in the first catalyst layer is 0.3 mg / cm by controlling the catalyst slurry wet film thickness. 2 .
[0053] Example 7: A method for preparing a battery membrane electrode
[0054] The difference between this embodiment and embodiment 1 is that the drying conditions of the first catalytic layer and the second catalytic layer are both 40° C. and 30 min.
[0055] Example 8: A method for preparing a battery membrane electrode
[0056] The difference between this comparative example and Example 1 is that the platinum loading in the second catalytic layer is 0.1 mg / cm by controlling the wet film thickness of the catalyst slurry. 2 .
[0057] Example 9: A method for preparing a battery membrane electrode
[0058] The difference between this comparative example and Example 1 is that a layer of graphene membrane is coated on the second catalytic layer and the proton exchange membrane, and the coating and drying process is consistent with that of the graphene membrane in Example 1.
[0059] Comparative Example 1: No graphene anti-stretching layer is applied
[0060] like Figure 3As shown, the difference between this comparative example and Example 1 is that no graphene layer is pre-coated between the proton exchange membrane 101 and the first catalytic layer 301, and the first catalytic layer 301 is directly coated on the proton exchange membrane, and the rest is the same as Example 1.
[0061] The second catalytic layer coating and drying process is shown in the picture Figure 4 As shown, it can be seen that without the protection of the graphene stretching layer, the proton exchange membrane swells severely and deforms significantly.
[0062] Comparison between Example 1 and Comparative Example 1
[0063] In Examples 1-9, the proton exchange membranes did not swell significantly when the second catalytic layer was applied, and the membrane electrodes obtained were of good quality. In contrast, in Comparative Example 1, the proton exchange membrane swelled severely when the second catalytic layer was applied, and the membrane electrodes obtained were of poor quality. It can be seen that a graphene layer is pre-coated between the first catalytic layer and the proton exchange membrane. Since graphene has high tensile strength, it can replace the back film to play an anti-stretching role. When the second catalytic layer is applied, the swelling of the proton exchange membrane can be effectively prevented, and a good-quality membrane electrode can be obtained.
[0064] The membrane electrode prepared in Example 1 and Comparative Example 1 was assembled into a single cell, wherein the first catalytic layer was used as an anode and the second catalytic layer was used as a cathode (the first catalytic layer could also be used as a cathode and the second catalytic layer as an anode). The cell performance and hydrogen permeation current density under hydrogen and oxygen conditions were evaluated under the same conditions with reference to GB / T20042.5-2009. The polarization curve and power density curve are shown in Table 1. Figure 5 The rated power of the membrane electrode prepared in Example 1 and Comparative Example 1 at 0.6V is 1.12W / cm 2 、0.47W / cm 2 The performance of the membrane electrode without graphene coating and serious deformation is much worse than that of the membrane electrode pre-coated with graphene; the hydrogen permeation current density of Example 1 and Comparative Example 1 is 0.12 mA / cm 2 , 0.32mA / cm 2 It can be seen that the membrane electrode prepared by pre-coating the graphene layer can effectively reduce the penetration of hydrogen from the anode to the cathode.
[0065] Comparative Example 2:
[0066] This comparative example is different from Example 1 in that the graphene in the graphene slurry is replaced with Cabot Vulcan XC-72R carbon black, and the rest is the same as Example 1.
[0067] During the coating and drying process of the second catalytic layer, the proton exchange membrane swelled significantly and deformed severely, indicating that the carbon black layer formed after the carbon black was dried had no anti-tensile effect.
[0068] Comparative Example 3
[0069] The difference between this comparative example and Example 1 is that no Nafion solution is added during the preparation of the graphene slurry, and the rest is the same as Example 1.
[0070] Due to the presence of the graphene film, the second catalyst layer has no obvious deformation during the coating and drying process, but when assembled into a single cell test, its rated power is 0.52W / cm 2 The power generation is significantly reduced compared to Example 1 because Nafion plays a role in conducting protons in the membrane layer. The absence of Nafion in the graphene membrane layer will affect the conduction of anode protons to the cathode and thus affect its power generation.
[0071] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A method for preparing a hydrogen fuel cell membrane electrode, characterized in that: include: A graphene membrane is coated between the proton exchange membrane and the first catalytic layer, wherein the graphene membrane is an anti-stretching layer, and when the second catalytic layer is coated, the graphene membrane is a backing membrane of the proton exchange membrane; Specifically include: Preparing graphene slurry and catalyst slurry, wherein the graphene slurry mainly comprises graphene, water and a commercial Nafion solution with a mass fraction of 5%; Fixing the proton exchange membrane, tearing off the protective film on the surface of the proton exchange membrane, retaining the back film, applying the graphene slurry on the proton exchange membrane and drying it, wherein the thickness of the graphene membrane after drying is 2 to 5 μm; A layer of catalyst slurry is coated on the graphene film obtained in the above steps and dried to obtain a first catalyst layer; After fixing the proton exchange membrane coated with the graphene membrane and the catalyst layer on one side, the back membrane is torn off, and the catalyst slurry is coated on the side without the membrane layer and then dried to obtain the second catalyst layer.
2. The preparation method according to claim 1, characterized in that: The thickness of the graphene film after drying is 2 or 5 μm.
3. The preparation method according to claim 1, characterized in that: A graphene membrane is coated between the second catalytic layer and the proton exchange membrane.
4. The preparation method according to claim 1, characterized in that: The solid content of Nafion in the graphene membrane is 20% to 30%.
5. The preparation method according to claim 1, characterized in that: The mass concentration of graphene in the graphene slurry is 10 mg / ml.
6. The preparation method according to claim 1, characterized in that: The raw materials of the first catalytic layer and the second catalytic layer are platinum-carbon catalyst, Nafion, water and isopropanol.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the carbon in the Nafion and the platinum carbon is 0.6 to 0.
8.
8. The preparation method according to claim 6, characterized in that: The mass ratio of the water to the isopropanol is 1:1 to 1:
5.
9. The preparation method according to claim 6, characterized in that: The platinum loading in the first catalytic layer and the second catalytic layer is 0.1-0.3 mg / cm 2 .
10. A hydrogen fuel cell membrane electrode, characterized in that: It comprises a proton exchange membrane, wherein both sides of the proton exchange membrane are coated with a catalytic layer, wherein a graphene membrane is coated between the catalytic layer on at least one side and the proton exchange membrane; The hydrogen fuel cell membrane electrode is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Catalyst slurry for membrane electrode, method for producing same, catalyst-coated membrane, and membrane electrode
CN112259753A
Method for preparing CCM through direct coating of cathode and anode
CN113299927A
Preparation of proton exchange membrane electrode for direct methanol fuel cell
CN111477922A